Propuesta de optimización del uso del agua potable en la i.e. 80824 "josé carlos mariátegui" el porvenir - Trujillo - 2014 - Roldán Santiago, Aurea Angelita (2016)
Optimization proposal was made in this investigation for use - drinking water in the I.E.80824 "Jose Carlos Mariategui" El Parvenir-Trujillo - Peru. It 2014. consisted in two stages: a) Proposal for an awareness program for the efficient use and recycling of water in the I.E. No. 0 80824 "JCM" so it was developed and a pretest and post test with a sample of 333 students at the primary level and secondary schools, 166 for the experimental group and 167 to the control group which were applied tabulated and processed using statistical measures as the arithmetic mean and standard deviation, which served as the basis for finding student t test with the pre and post test was compared. b) A model of recycling water was proposed in the I.E. 80824 "Jose Carlos Mariategui". The attitude of schoolchildren against the efficient use of drinking water in the S.I. 80824 "Jose Carlos Mariategui" before the proposal reached 11.21 points and after application of the proposal improved significantly up to 16.34 points. The attitude of school versus recycling of drinking water in the E.I. 80824 "Jose Carlos Mariategui" before the proposal reached 12.21 points and after application of the proposal improved significantly up to 17.21 points. The techniques used for data collection were interview: Direct observation. The methods used were the quantitative, descriptive and statistical methods: descriptive and analytical statistics was applied to determine frequency of the variables; for this, the simple input boxes describing the problematic reality of that institution was used. Subsequently, interviews with students and parents where the first source information was collected were made. Two questionnaires validating the judgment of experts to evaluate the efficient use of water and water recycling were developed.